Pedoman Praktis Penyusunan Kamus Kompetensi Teknis Aparatur Sipil Negara - Wahyuadianto, Agus; Saputro, Hendra Nugroho (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
Competency dictionary and job standard for Indonesian civil servant has been exposed in The Decree of Ministry of Administrative and Bureaucratic Reform Number 38 Year of 2017. This decree gives ample explanation on managerial and social-cultural competencies, including the exact lists of competency titles and the application toward each job level. On the other hand, the similar treatment does not applied toward technical competency, only general guidance included. Since all ministries and non-ministerial government institutions must develop technical competency dictionary and job standard for their own governmental affairs, thus the need of the guidance is heightened. This study aims for creating practical guidance in developing technical competency dictionary along with the example. Qualitative approach with case study was used in this study. Moreover, data was gathered through literature examination, focus group discussion, and workshop. As the result, there are three steps in developing technical competency dictionary, ie: (1) identifying technical competency title using organization main duties and function cascading technique; (2) deciding technical competency levels using Taxonomy Bloom theory; and (3) writing down compatible behaviour indicators using guidance matrix. In addition, example provided for every step in order to ease the guidance practicality. Hopefully, this practical guidance could help human resource practitioner in developing technical competency dictionary, especially in Indonesian civil servant context. Furthermore, this article will add different perspective toward competency studies.